ПСИХИКАЛЫҚ ЖАҚТАН АРТТА ҚАЛҒАН БАЛАЛАРДЫҢ ПСИХОЛОГИЯЛЫҚ өзгешеликлери - Шеримбетова, З.Ш. (FAN va JAMIYAT, 2018)
In the article are considered psychological features of children with deviations in mental development. There is given the short analysis of the problem by the scientists psychologists. The psycho correctional works, carried out by them are described. Besides, the author gives recommendations to the teachers of schools.